Pengaruh Ukuran Perusahaan, Profitabilitas, dan Risiko Perbankan terhadap Perekayasaan Laba - Kustono, Alwan Sri (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2010)
This study was aimed to analyze the influence of firm size, profitability dan company risk towards account manipulationon bankin Indonesia. This study was performed using field research. Data were collected from Indonesian Bank Directories. Sample in this study is 25 banksfrom 2000-2006 and is derived using some criteria. This study used linier regression technique.The result showed that risk of firm influenced income smoothing practices. The findings refused second hypothesis. The study contributed to the literature in that higher risk of bank drive to increase the account manipulation tendency. Key words: income smoothing, firm size, profitability, risk of the firm